(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to formulate an integrative model based on ontology, epistemology, and axiology (OEA) as a philosophical foundation for pesantren scientific management that is relevant to curriculum development and Islamic educational practices in the modern era. The research uses a library research approach with a layered philosophical hermeneutics method through a triple hermeneutic circle. Data sources include classical Islamic works, namely Iḥyā’ ’Ulūm al-Dīn by al-Ghazālī, Muqaddimah by Ibn Khaldun, Prolegomena by Syed Muhammad Naquib al-Attas, and the concept of Maqāṣid al-Sharī’ah al-Shāṭibī, as well as 27 reputable scientific articles from the Scopus and SINTA databases ranked 3–6 published in the period 2019–2025. The results of the study show that pesantren scientific management is built on the integration of three main dimensions: ontological, which views knowledge as a unity of revelation, reason, and spirituality; epistemological, which emphasises scientific transmission based on sanad, scientific rigour, and epistemic awareness; and axiological, which is oriented towards character building and social responsibility. The resulting OEA model provides a conceptual and operational framework for the development of a holistic curriculum, relational pedagogy, and pesantren management that is adaptive to global and digital dynamics